2002
DOI: 10.1046/j.1440-1746.17.s3.28.x
|View full text |Cite
|
Sign up to set email alerts
|

A new enzyme immunoassay for the detection of antibody to hepatitis E virus

Abstract: The new HEV EIA developed in the present study is a highly specific diagnostic assay for the detection of anti-HEV activity in serum specimens obtained from different epidemiologic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
2
16
0
2
Order By: Relevance
“…These findings are consistent with other reports where genotype 1 antigens are found to react equally well with serum samples from both primates and patients infected with the four known genotypes of HEV (12,19). Although in general lower reactivity in HEV genotype 3-infected patients was seen compared to genotype 1 infections, we conclude that the currently used assays are acceptable for testing suspected genotype 1 and 3 HEV infections in patients in settings of low endemicity.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with other reports where genotype 1 antigens are found to react equally well with serum samples from both primates and patients infected with the four known genotypes of HEV (12,19). Although in general lower reactivity in HEV genotype 3-infected patients was seen compared to genotype 1 infections, we conclude that the currently used assays are acceptable for testing suspected genotype 1 and 3 HEV infections in patients in settings of low endemicity.…”
Section: Discussionsupporting
confidence: 92%
“…The other protein, MPII, is composed of strong and broad immunoreactive antigenic epitopes, some of which (ORF3 epitopes) are derived from two different HEV genotypes: the Mexico and Burma HEV strains (Khudyakov et al 1993(Khudyakov et al , 1994. It was shown that the combination of these two antigens can be used as a very efficient diagnostic target suitable for the reliable detection of HEV-specific antibodies in different epidemiological settings (Obriadina et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of IgG anti-HEV -Serum samples were tested for IgG anti-HEV by EIA according to the method described previously and standardized by Obriadina et al (2002) that uses two HEV recombinant proteins, a mosaic protein (MP-II) and a protein containing region 452-617 aa of the ORF2 of the HEV Burma strain as coating antigens. When applied to detection of HEV antibodies in animal sera, this EIA protocol was modified by using species-specific anti-IgG horseseradish peroxidase enzyme conjugates (anti-IgG-HRP, Sigma Chemicals St. Louis, MO) for serum samples representing respective species.…”
Section: Methodsmentioning
confidence: 99%
“…These assays have varied significantly (16), and assays based on open reading frame 2 (ORF2) were shown to be more sensitive in detecting anti-HEV than those based on ORF3 (1,11,17). These recombinant-protein-based tests have detected anti-HEV in 90 to 95% of symptomatic HEV cases (3,10…”
mentioning
confidence: 99%